KAJIAN HOTS (HIGH ORGER THINKING SKILL) DAN KAITANNYA DENGAN BERPIKIR ANALITIS - Devariyani Syavarizca; Sumaji Sumaji (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
HOTS (High Order Thinking Skill) is an skill that every student must have. Because HOTS (High Order Thinking Skill) very complex and require every student to think more than memorizing facts or concepts. The purpose of this study is to search the relationship between HOTS (High Order Thinking Skill) with analytical thinking. Where analytical thinking is one of the important thinking skills for every student. Analytical thinking make it easy for student to think logically and structured. This research is a literature study. The methodology used is collecting written material from books, journals. Articles that discuss about HOTS (High Order Thinking Skill) and analytical thinking. The result of the literature study show that analytical thinking is part of HOTS (High Order Thinking Skill). This is corresponding with the revision of Bloom’s Taxonomy by Krathwohl, analytical thinking ranks fourth in the cognitive or commonly known as C-4. In addition, indicators of analytical thinking/analyzing by Krathwohl and Anderson with the indicators of analytical thinking by Bloom have similarities. We can see when a mathematical problem type C-4 is elaborated by analyzing it, it will be seen that this indicator has same purpose in accordance with the understanding of analytical/analyzing that is breaking down the elements into smaller elemens and looking for the relationship of each of these elements. So it can be concluded that analytical thinking is HOTS (High Order Thinking Skill).